The Combined Impact of Canopy Stability and Soil NOx Exchange on Ozone Removal in a Temperate Deciduous Forest. Issue 10 (5th October 2022) - Visser, Auke J.; Ganzeveld, Laurens N.; Finco, Angelo; Krol, Maarten C.; Marzuoli, Riccardo; Boersma, K. Folkert
Abstract: Dry deposition is an important ozone sink that impacts ecosystem carbon and water cycling. Ozone dry deposition in forests is regulated by vertical transport, stomatal uptake, and non‐stomatal processes including chemical removal. However, accurate descriptions of these processes in deposition parameterizations are hindered by sparse observational constraints on individual sink terms. Here we quantify the contribution of canopy‐atmosphere turbulent exchange and chemical ozone removal by soil‐emitted nitric oxide (NO) to ozone deposition in a North‐Italian broadleaf deciduous forest. We apply a multi‐layer canopy exchange model to interpret campaign observations of nitrogen oxides (NO x  = NO + NO2 ) and ozone exchange above and inside the forest canopy. Two state‐of‐science parameterizations of in‐canopy vertical diffusivity, based on above‐canopy wind speed or stability, do not reproduce the observed exchange suppressed by canopy‐top radiative heating, resulting in overestimated dry deposition velocities of 10%–19% during daytime. Applying observation‐derived vertical diffusivities in our simulations largely resolves this overestimation. Soil emissions are an important NO x source despite the observed high background NO x levels. Soil NO x emissions decrease the gradient between canopy and surface layer NO x mixing ratios, which suppresses simulated NO x deposition by 80% compared to a sensitivity simulation without soil emissions. However, a sensitivity analysis shows that the enhanced chemical ozone sink by reaction with soil‐emitted NO is offset by increased vertical ozone transport from aloft and suppressed dry deposition. Our results highlight the need for targeted observations of non‐stomatal ozone removal and turbulence‐resolving deposition simulations to improve quantification and model representation of forest ozone deposition. Plain Language Summary: Ozone is a harmful air pollutant that impacts human and ecosystem health. Ozone can be removed by forest ecosystems as a result of air transport into forests followed by plant ozone uptake or chemical removal, but quantifying these individual processes is difficult. We combine model simulations and treetop measurements to study the role of vertical forest‐atmosphere air transport and chemical ozone removal inside the forest. We find that our model can only reproduce surface ozone removal if we account for suppressed transport as derived from observations. The soil is a substantial source of nitric oxide (NO) that reacts with ozone. According to our analysis, the presence of a soil NO source does not lead to increased ozone removal because other ozone sinks are reduced. Our results suggest that individual ozone removal processes in forests can best be studied using targeted observations and models that better resolve forest‐atmosphere exchange. Key Points: We use a multi‐layer canopy‐atmosphere exchange model to interpret ozone flux observations inside and above a North‐Italian forest Two state‐of‐science vertical exchange parameterizations do not capture in‐canopy stable stratification suppressing ozone deposition Soil nitric oxide emissions do not increase ozone deposition due to compensating effects by deposition and transport